Study of amphiphilic polyester micelles by hyper-rayleigh scattering: Invertibility and phase transfer - Peukert, Wolfgang; Martinez Tomalino, Lars-Owe; Voronov, Andriy; Kohut, Ananiy (Journal of Physical Chemistry B, 2008)
For the first time, hyper-Rayleigh scattering (HRS) of invertible polymeric micellar structures has been measured. HRS measurements on amphophilic invertible polyesters with alternating hydrophilic and hydrophobic fragments were carried out in solvents of differing polarity. The observed strong variation of the HRS signals is attributed to the switching behavior of the polyester micelles in the different solvents. The hyperpolarizabilities and the size of the micelles increased with decreasing polarity of the solvent. Observing the dynamics of the solubilization of an insoluble dye (malachite green) by the invertible polyester in toluene confirmed the possibility to reveal conformational changes in polyester macromolecules by HRS. In contrast to UV measurements which showed a continuous increase in absorbance and indicated overall solubilization of the dye, the HRS signals decreased after approaching a maximum value. The decrease of the HRS signals is attributed to the change of dye molecules' orientation within the micelles due to the change of polymeric conformation in toluene. The results have shown that HRS is sensitive to reorientation and ordering of the macromolecules and might become a powerful tool for studying polymer micellar structures as well as phase transfer processes at the nanoscale. © 2008 American Chemical Society.
Keywords: rayleigh; scattering; polymer; structure; polarizability; hydrophilic; hydrophobic